Comparative Nutritive Value of Meat in Commercial Native Chicken, Backyard Native Chicken, Commercial Broiler and Spent Layer Chicken: 10.5958/2581-6616.2020.00002.X - kumar, R. Sathish; Kulkarni, V. V.; Vasan , P. (Journal of Meat Science, 2021)
A study was planned on the nutritive value of meat in commercial native chicken (CNC), backyard native chicken (BNC), commercial  broiler (CB) and spent layer chicken (SLC). An experiment was conducted on 12 birds of either sex in each class. Birds were slaughtered  by Jatka method and nutritional composition and protein quality of each group were studied for breast and leg meat separately. Pro tein quality (biological value, true digestibility and net protein utility) of meat was studied by precision feeding trial in adult cockerels.  Cholesterol content was significantly lower in CB and CNC. The true digestibility, biological value and net protein utility in SLC were  significantly lower than other categories. Biological value and net protein utility was significantly higher (P
Keywords: Biological Value; Composition; Meat Quality; Nutritive value; Poultry